Lower Rate of Seropositivity to Measles Among Young Healthcare Personnel in New York City. (1st June 2020) - Lucca, Anabella; Bayoumi, Nagla; Ramanathan, Lakshmi V; Sepkowitz, Kent; Kamboj, Mini
Abstract: We examined the prevalence of measles antibody among 12 349 newly hired HCP between 2009 and 2019. Younger HCP were significantly more likely to have no immunity. Compared with a 92.2% seropositive rate among 1057 persons hired at age >50 years, only 84.4% of approximately 10 000 HCP aged <40 years had protective antibody.